2014
DOI: 10.1080/19404158.2014.891531
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Malay word structure by pre-service special education teachers: foundation-level knowledge for remedial instruction

Abstract: Pre-service special educators' Malay word structure knowledge was assessed through their analysis of words. A total of 69 participants analysed a vocabulary list based on a set of criteria formulated from the Malay language word structure. Results indicated that they were able to count syllables and phonemes, and identify types of affixations; however, they were unable to identify syllabic structures and word categories accurately. The morphemic and phonetic structure of words also had a moderating effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Due to a lack of freely available objective language proficiency test in past research has resorted to estimating Malay proficiency using self-reported measures such as order of language acquisition (e.g., Lee & Low, 2014;Yap et al, 2017) or self-ratings (e.g., Jalil et al, 2011;Rahman et al, 2018;Rusli & Montgomery, 2020). However, considering most of the Malaysian Malay L2 speakers have a rather uniform age of Malay acquisition due to compulsory language education in school and their diverse language use and experience (Jin et al, 2013), individual differences in language proficiency of the bilingual or multilingual speakers can be difficult to assess based on just self-reported information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a lack of freely available objective language proficiency test in past research has resorted to estimating Malay proficiency using self-reported measures such as order of language acquisition (e.g., Lee & Low, 2014;Yap et al, 2017) or self-ratings (e.g., Jalil et al, 2011;Rahman et al, 2018;Rusli & Montgomery, 2020). However, considering most of the Malaysian Malay L2 speakers have a rather uniform age of Malay acquisition due to compulsory language education in school and their diverse language use and experience (Jin et al, 2013), individual differences in language proficiency of the bilingual or multilingual speakers can be difficult to assess based on just self-reported information.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that involved Malay-speaking bilinguals have so far either assumed "native-like" proficiency of Malay L1 speakers (e.g., Lee & Low, 2014;Yap et al, 2017), or used selfratings to estimate the speakers' language proficiency (e.g., Jalil et al, 2011;Rahman et al, 2018;Rusli & Montgomery, 2020). However, the assumption of "native-like" proficiency is not always reliable because the language proficiency of L1 speakers (e.g., vocabulary size) could vary substantially according to the speakers' language experience (e.g., whether a person reads) (Brysbaert et al, 2016;Hulstijn, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative that elementary teachers to have necessary knowledge of the structure of language and the alphabetic writing system in order to provide remedial instruction as needed (Lee, L.W. & Low, H.M., 2014).…”
Section: Remedial Educationmentioning
confidence: 99%